2021
DOI: 10.3389/fonc.2021.618908
|View full text |Cite
|
Sign up to set email alerts
|

CS2164 and Venetoclax Show Synergistic Antitumoral Activities in High Grade B-Cell Lymphomas With MYC and BCL2 Rearrangements

Abstract: High-grade B-cell lymphoma with concurrent MYC and BCL2 rearrangements (HGBL-DHL) is a rare, aggressive mature B-cell malignancy with a high likelihood of treatment failure following front-line immunochemotherapies. Patients with HGBL-DHL who develop a relapsed or refractory disease have little effective therapeutic strategies and show very poor clinical outcomes, thus calling for development of novel therapies for this specific patient population. In this study, we investigated the preclinical anti-lymphoma e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that HDAC inhibitors could induce apoptosis through interference with cytoprotective DDR [40]. In addition, venetoclax can trigger DNA damage by weakening Rad51-meidiated DNA damage repair [41]. Thus, we hypothesized that the DNA damage induced by the combination of the two agents might contribute to the synergistic anti-myeloma effect of the two drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HDAC inhibitors could induce apoptosis through interference with cytoprotective DDR [40]. In addition, venetoclax can trigger DNA damage by weakening Rad51-meidiated DNA damage repair [41]. Thus, we hypothesized that the DNA damage induced by the combination of the two agents might contribute to the synergistic anti-myeloma effect of the two drugs.…”
Section: Discussionmentioning
confidence: 99%
“…40 In addition, venetoclax can trigger DNA damage by weakening Rad51-meidiated DNA damage repair. 41 Thus, we hypothesized that the DNA damage induced by the combination of the two agents might contribute to the synergistic anti-myeloma effect of the two drugs. Accordingly, our results shown coexposure to chidamide and venetoclax led to a sharp increase of γH2A.X, a typical marker of DSB.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al observed a potential role of CS2164 for the treatment of NHLs through the perturbation of multiple signaling cascades (angiogenesis, inflammation and proliferation) by inhibiting the following kinases: vascular endothelial growth factor receptor 1-3 (VEGFR1, VEGFR2 and VEGFR3), platelet-derived growth factor receptor alpha (PDGFRα), receptor tyrosine kinase (c-Kit), kinase Aurora B (AURKB), and chronic inflammation-related kinase (CSF-1R). Specifically, CS2164 showed superior anti-lymphoma activity against MYC-arranged BL models, suggesting it could also have a cytotoxic effect on other MYC-altered malignancies [102] . Following these observations, Yuan et al [103] assessed the efficacy of this novel agent in combination with venetoclax using HGBL in vitro and in vivo models, where they could demonstrate a reduction of MYC and BCL2 protein levels, as well as antitumor efficacy with tolerable toxicities in a xenograft mouse model with MCA cells.…”
Section: Other Inhibitors and Degradersmentioning
confidence: 99%